UPAYA PENINGKATAN MUTU PELAYANAN MEDIS PADA PEMBUATAN STANDAR PROSEDUR OPERASIONAL PELAYANAN MEDIS DI RSIA ‘AISYIYAH KLATEN - Susi Salmah; Susanto Susanto (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Quality is a total picture of the nature of a product or service which is able to give satisfaction. The quality of hospital services can be measured by using the standard operating procedures (SOPs) which are the instructions made together to carry out routine activities based on professional standards. The purpose of this research is to analyze the efforts to improve the quality of medical services in RSIA (Child and Maternity Hospital) ‘Aisyiyah Klaten related to the doctor’s knowledge of the philosophy of making SOPs for Medical Services. Methods: The study design was a case study with a qualitative and quantitative approach. It was conducted by in-depth interviews with directors, the chairman of the medical committee, the secretary of the medical committee and the special staff of directors relating to the medical committee and making of SOPs for Medical Services. The questionnaire is addressed to all the doctors associated with the knowledge, attitudes and behavior in making the SOPs for Medical Services. Analysis of the data is presented descriptively from the perspective of input, process and output. Results and discussion: The results obtained on the input which is the vision to become the recommended hospital with the mission of providing services in accordance with medical and administrative standards of professional and accredited. There are meeting facilities, budget, commitments director on the decree on the medical committee and the accreditation team. From the process side, the meeting attendance of accreditation team doctors is 62.90%, non- accreditation team specialists by 50%, non-accreditation team general practitioners by 18.18%. The making of the meeting minutes reaches 100%. On the SOPs of Medical Services, the value of all the doctor's knowledge is 90.68%, the value of all the doctor's attitude is 84.78% and the value of the behavior of all doctors is 63.37%. From the output side, the number of SOPs of Medical Services which have been made are 31 types (88.24%). The number of SPOs which was passed are 50 titles (43.10%). There are constraints on the time and the ability of doctors. Conclusion: RSIA ‘Aisyiyah Klaten has undertaken efforts to improve medical services quality in making the SOPs for Medical Services through a systems approach well and the doctors already understand the philosophy of making good SOPs for Medical Services.